A Facile Synthesis of Highly Nitrogen-Doped Carbon Dots for Imaging and Detection in Biological Samples - Qianchun Zhang; Siqi Xie; Yanqun Yang; Yun Wu; Xingyi Wang; Jincheng Wu; Li Zhang; Junyu Chen; Yuan Wang (Journal of Analytical Methods in Chemistry)
A facile, green, and high-output hydrothermal synthesis was proposed for the fabrication of highly fluorescent nitrogen-doped carbon quantum dots (N-doped CDs). The nitrogen content in N-doped CDs reached 19.2% and demonstrated strong blue fluorescence emission was obtained with fluorescence quantum yield (QY) of up to 32.9%, which exhibit high fluorescence quantum yield, high photostability, and excellent biocompatibility. The N-doped CDs possess high photostability, low toxicity, and excellent biocompatibility, based on which the N-doped CDs were successfully applied as a fluorescence probe for cell imaging. Moreover, it was then successfully demonstrated for sensitive and selective detection of Fe3+ in serum.